PLACE OF RISK MANAGEMENT IN THE BUSINESS PLANNING PROCESS - E. Pravkina (Publishing House of the State University of Management, 2016)
Now the activities of oil companies based on the business plan. It is the primary source for decision-making. To improve efficiency and improve financial results companies must identify risks, the risk register should be the basis of a business plan.